Examining the Leadership Molecule: An Empirical Study of Key Leadership Roles in Rapidly Growing Entrepreneurial Businesses - Flamholtz, Eric; Kannan-Narasimhan, Rangapriya (Senate Hall, 2013)
Previous theory and research has focused upon opportunity seeking behavior as the essence of entrepreneurial leadership, and neglected the role of advantage-seeking behavior by leaders. However opportunity seeking behaviors alone are insufficient to enable businesses reach the next stages of growth. A previous paper has suggested five specific roles that enable leaders to maximize both opportunity seeking as well as advantage seeking behaviors. These five roles are executed by a team rather than a single individual comprising what has been termed a "Leadership Molecule". In this study, we empirically test the Leadership Molecule hypothesis by developing and validating a scale for measuring the Leadership Molecule. We use data from 213 participants from 26 rapidly growing entrepreneurial small businesses based in China*. Factor analyses results confirm the existence of a Leadership Molecule. The scale had a high internal reliability (Cronbach's α= .91) and showed good convergent, discriminant and criterion related validity Keywords: Leadership Molecule, Leadership Molecule Scale, Organizational effectiveness, Growing pains, Reliability, Validity
Keywords: leadership molecule|leadership molecule scale|organizational effectiveness|growing pains|reliability|validity